Does Audit Quality Moderate the Relationship Between Corporate Social Responsibility and Tax Avoidance? - Jerri Benardus Dharmana; Rino Tam Cahyadi; Lalu Rahmat Sohdi (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines the effect of Corporate Social Responsibility (CSR) on tax avoidance and the moderating role of Big 4 audit quality within the Indonesian mining and energy sector. Using the Effective Tax Rate (ETR) as an inverse proxy for tax avoidance, the results reveal that extensive CSR disclosures significantly increase ETR, thereby actively reducing tax avoidance behavior. This major finding strongly supports legitimacy theory, demonstrating that environmentally sensitive firms utilize integrated social transparency and tax compliance to satisfy societal expectations, mitigate reputational risks, and secure their operational license. Conversely, the statistical analysis indicates that Big 4 audit quality fails to moderate this relationship, which contradicts traditional agency theory expectations regarding external governance. This lack of moderation demonstrates that in a highly complex and capital-intensive sector, external auditors function primarily to provide professional assurance on financial statement fairness rather than intervening in or restructuring strategic corporate tax planning. Consequently, tax policy remains a strictly internal managerial decision, and elite external oversight does not automatically enhance the impact of social commitments on tax compliance.